Interfacial Hydrogen Bonds and Their Influence Mechanism on Increasing the Thermal Stability of Nano-SiO(2)-Modified Meta-Aramid Fibres - Tang, Chao (Polymers (Basel), 2017)
For further analysis of the effect of nano-doping on the properties of high polymers and research into the mechanism behind modified interfacial hydrogen bonds, a study on the formation probability of nano-SiO(2)/meta-aramid fibre interfacial hydrogen bonds and the strengthening mechanism behind interfacial hydrogen bonds on the thermal stability of meta-aramid fibres using molecular dynamics is performed in this paper. First, the pure meta-aramid fibre and nano-SiO(2)/meta-aramid fibre mixed models with nanoparticle radiuses of 3, 5, 7 and 9 Å (1 Å = 10(−1) nm) are built, and then the optimization process and dynamics simulation of the models are conducted. The dynamics simulation results indicate that the number of hydrogen bonds increase due to the doping by nano-SiO(2) and that the number of interfacial hydrogen bonds increases with the nanoparticle radius. By analysing the hydrogen bond formation probability of all the atom pairs in the mixed model with pair correlation functions (PCFs), it can be observed that the hydrogen bond formation probability between the oxygen atom and hydrogen atom on the nanoparticle surface is the greatest. An effective way to increase the number of interfacial hydrogen bonds in nano-SiO(2) and meta-aramid fibres is to increase the number of hydrogen atoms on the nano-silica surface and oxygen atoms in the meta-aramid fibre. By using the radial distribution function (RDF), the conclusion can be further drawn that the hydrogen bond formation probability is at a maximum when the atomic distance is 2.7–2.8 Å; therefore, increasing the number of atoms within this range can significantly increase the formation probability of hydrogen bonds. According to the results of chain movement, the existence of interfacial hydrogen bonds effectively limits the free movement of the molecular chains of meta-aramid fibres and enhances the thermal stability of meta-aramid fibres. The existence of interfacial hydrogen bonds is one of the important reasons for formation of the stable interface structure between nanoparticles and meta-aramid fibres. In addition, a nanoparticle with a small radius improves the interfacial hydrogen bond energy density and interfacial interaction energy density, enhancing the stability of the mixed model interface.